CHALLENGES OF TEACHING MIXED-ABILITY EFL CLASSES: A STUDY OF TWO PRIVATE SCHOOLS - Daneth Heng; Sina Pang; Sereyrath Em (PROJECT (Professional Journal of English Education), 2023)
English teaching and learning were first encouraged in Cambodia between 1970 and 1975. However, it then disappeared until 1989. During the last decade, English has become Cambodia's most prominent foreign language. The popularity and vital roles of English in Cambodia's political and economic development have then resulted in the establishment of many private English as a Foreign Language  (EFL) schools across the nation. English teaching and learning at these private EFL schools have various challenges. Mixed-ability classes, one of the challenging issues, are still common in many of these EFL schools. As these private EFL schools have played important roles in English education in Cambodia, it is interesting to learn more about their teachers' challenges in instructing mixed-ability students and their teaching strategies for mixed-ability classes. The current study involves 20 male and 30 female teachers who were teaching at two private EFL schools in Phnom Penh, Cambodia. A survey questionnaire was used to collect data from them. The findings proved that these EFL teachers had many challenges dealing with mixed-ability classes, and appropriate and immediate actions from their school management team were required. Thus, effective classroom management and a variety of teaching methods were applied in mixed-ability classrooms. Besides, teachers' experience did not affect the strategies’ effectiveness. The present study also suggests that a future study be carried out with a large sample size at various locations. The use of various forms, including qualitative and mixed techniques, is also encouraged. It is also advised to consider how students view courses with diverse ability levels.Keywords: Challenges; EFL Classes; Mixed-Ability Students; Private School; Cambodia